Fast and live virtual machine migration in data center networks - Teng MA; Yuxiang HU (Dianxin kexue)
In data center networks,virtual machine live migration causes large volume of data transfer on core links of the network,which leads to performance degradation of the baring application and other background services.Based on inheriting the existing memory page de-duplication technique,a new search structure was presented composed of a counting Bloom filter with each bucket pointing to a link list,which overcame the problem of false positive of memory page lookup.Furthermore,a pruned algorithm was proposed to reduce the length of each link list and accelerate the lookup as much as possible to accomplish live and fast virtual machine migration in rack level.Experiment results show that the proposed method transfers less data on core links,takes less time to finish migration,and decreases the degradation of network applications caused by migration.